Efficiency of Nano powders of Cloves, Cinnamon, and Turmeric in Ochratoxin A (OTA) production by Penicillium polonicum - Al-Tamimi , Salam Nsaif; Hawar , Sumaiya Naeema (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The study aimed to evaluate the efficiency of Nano powders of Cloves, Cinnamon, and Turmeric in inhibiting fungal growth and Ochratoxin a (OTA) production by Penicillium polonicum and reducing the toxin in liquid media. The research highlights the reduction of ochratoxin toxins using environmentally friendly plant Nano powders that are safe for human and animal consumption. They are mainly used in food as flavorings and preservatives. The Nano treatments of cloves, cinnamon, and the mixture (Cloves-Cinnamon-Turmeric) achieved complete inhibition of fungal growth and OTA toxin production by 100% for concentrations (2, 4, 6, 8%). The treatment of Nano Turmeric powder did not inhibit fungal growth at all concentrations. However, it inhibited OTA toxin production by 87 and 92% for concentrations 2 and 4% and by 100% for both concentrations 6 and 8%. In reducing OTA toxin, the mixture (Cloves-Cinnamon-Turmeric) was superior, with reduction rates of 95% for concentration 2% and 100% for concentrations 4, 6, and 8%. It was followed by the treatment of Clove Nano powder with reduction rates of 78, 84, 89, 94, and 100% for concentrations 0.8, 2, 4, 6 and 8% respectively. The treatment of Turmeric Nano powder came in third place in the efficiency of reducing OTA toxin with rates of 74, 79, 83, 87, and 100% for the same concentrations, respectively. As for Cinnamon Nano powder, it showed reduction rates of 68, 71, 79, 85 and 91% for the same concentrations, respectively